Comparison of the effects of retroperitoneoscopic ureterolithotomy and ureteroscopic lithotripsy in the treatment of upper ureteral calculi. Issue 38 (24th September 2021) - Gao, Sheng-Lin; Wu, Hao; Su, Quan-Xin; Zhang, Zi-Yi; Zhang, Ze; Lu, Chao; Zhang, Li-Feng; Zuo, Li
Abstract : Abstract: This study compares the efficacy of retroperitoneoscopic ureterolithotomy (RPUL) and ureteroscopic lithotripsy (URL) in the treatment of upper ureteral calculi. The clinical data of 150 patients with upper ureteral calculi who underwent RPUL and 136 patients who underwent URL between January 2014 and October 2019 were retrospectively analyzed. The operation time, postoperative hospital stay, operation success rate, stone clearance rate, and surgical complications were evaluated between the two groups. For the RPUL and URL groups, respectively, the average operation time was 74.5 ± 24.6 minutes and 54.5 ± 13.2 minutes; the postoperative hospital stay was 5.8 ± 1.4 days and 3.2 ± 1.2 days; the operation success rate was 96.0% (144/150) and 85.3% (116/136); the incidence rate of complications was 3.5% (5/144) and 17.5% (18/103); and the stone clearance rate was 100% (144/144) and 88.8% (103/116), which were all statistically significant ( P < .05). Both RPUL and URL had the advantages of low trauma and fast recovery rate for patients with upper ureteral calculi. However, patients who underwent RPUL showed higher success and fewer complication rate. RPUL might be a safe and effective laparoscopic method for the treatment of patients with upper ureteral calculi.